World development report 2003 : sustainable development in a dynamic world; transforming institutions, growth, and quality of life (Oxford : The World Bank / Oxford University Press, 2003)
Economics
Keywords: World development report; Portfolio; Innovation; Migration; Livelihood; Agricultural land